Marguerite de Navarre, a Nicodemite? Adiaphora and Intention in Heptaméron 30, 65, and 72 - Francis, Scott (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2016)
This article situates Marguerite de Navarre’s Heptaméron within the reformist debate over adiaphora, or theologically indifferent matters made righteous or sinful by the believer’s intentions and conscience. It discusses how adiaphora and their implications for Christian liberty and Catholic devotional practices are understood differently by the schismatic reformers (Luther and Calvin) and the non-schismatic reformers (Erasmus, Lefèvre, Roussel), and how Marguerite ultimately sides with the latter in Tales 30, 65, and 72 of the Heptaméron, which emphasize the primacy of intention and conscience over external ceremony. Through the debates among the discussants, Marguerite also uses the opacity of intention to counter the refusal of Calvin and his followers to recognize as adiaphora Catholic practices they regarded as idolatrous, such as placing votive candles in front of statues.